X-6-2x=2

Simple and best practice solution for X-6-2x=2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X-6-2x=2 equation:



X-6-2X=2
We move all terms to the left:
X-6-2X-(2)=0
We add all the numbers together, and all the variables
-1X-8=0
We move all terms containing X to the left, all other terms to the right
-X=8
X=8/-1
X=-8

See similar equations:

| 8+6n=13+5n | | 5(x+2)-2=4x+10 | | 3(x+5)=2x+ | | 8/10=y/10 | | 5.62=2.3t | | 5/16=-3/32+7/8n | | n+5-9n=8-2n-3 | | -241.5=-7(14+5m) | | 210=n(n+1)/2 | | X+23=x=27 | | -1=(-4)+q | | 6=4+2(x+7) | | |x|-10=-2 | | 5x(3x)=0 | | -(9s+12)=-3 | | a/2-8=-17 | | 21z=31 | | -4(1x-6)=24 | | 2(2x)+6-3x=-3= | | 4^(x+3)=152 | | 108.50-x=5.50 | | 40,000/1,000x=60,000 | | 6b^+9=177 | | -9.8+x/3.4=7.3 | | 5z-14=3z-8 | | 61+82+(9x+1)=180 | | 2n+19=3n+21 | | 6b^-12b=0 | | -5×-10y=-30 | | 4x+20x-8=-2(-12x+8) | | 3(g+4)-8=-19= | | 5/13=k4/39 |

Equations solver categories